Revision of the type species of Metroperiella (Bryozoa, Cheilostomatida), with the description of two new species. Issue 3 (25th January 2019) - Berning, Björn; Achilleos, Katerina; Wisshak, Max
ABSTRACT: We here fix the types of Schizoporella lepralioides Calvet in Jullien and Calvet, type species of the genus Metroperiella Canu & Bassler, and redescribe the species based on scanning electron microscope examination. Metroperiella populations from the Mediterranean Sea, which have hitherto been regarded as conspecific with Metroperiella lepralioides, are introduced as a new species, Metroperiella mesogeia sp. nov. Accordingly, the geographic distribution of M. lepralioides is restricted to its type locality, the Azores Archipelago (central North Atlantic). Another species, Metroperiella porellidesia sp. nov., which occurs sympatrically with M. lepralioides, is also newly described. urn:lsid:zoobank.org:pub:523EA5DE-B023-48ED-8D85-37CAF5475164